Safety and Efficacy of Prehospital Diltiazem for Atrial Fibrillation with Rapid Ventricular Response. Issue 3 (2nd May 2019) - Rodriguez, Alexa; Hunter, Christopher L.; Premuroso, Caitlin; Silvestri, Salvatore; Stone, Amanda; Miller, Stacie; Zuver, Christian; Papa, Linda
Abstract: Introduction: Atrial fibrillation (AFIB) with rapid ventricular response (RVR) is a common tachydysrhythmia encountered by Emergency Medical Services (EMS). Current guidelines suggest rate control in stable, symptomatic patients. Problem: Little is known about the safety or efficacy of rate-controlling medications given by prehospital providers. This study assessed a protocol for prehospital administration of diltiazem in the setting of AFIB with RVR for provider protocol compliance, patient clinical improvement, and associated adverse events. Methods: This was a retrospective, cohort study of patients who were administered diltiazem by providers in the Orange County EMS System (Florida USA) over a two-year period. The protocol directed a 0.25mg/kg dose of diltiazem (maximum of 20mg) for stable, symptomatic patients in AFIB with RVR at a rate of >150 beats per minute (bpm) with a narrow complex. Data collected included patient characteristics, vital signs, electrocardiogram (ECG) rhythm before and after diltiazem, and need for rescue or additional medications. Adverse events were defined as systolic blood pressure <90mmHg or administration of intravenous fluid after diltiazem administration. Clinical improvement was defined as a heart rate decreased by 20% or less than 100bmp. Original prehospital ECG rhythm interpretations were compared to physician interpretations performed retrospectively. Results: Over the study period, 197 patients received diltiazem, with 131 adhering to the protocol. The initial rhythm was AFIB with RVR in 93% of the patients (five percent atrial flutter, two percent supraventricular tachycardia, and one percent sinus tachycardia). The agreement between prehospital and physician rhythm interpretation was 92%, with a Kappa value of 0.454 (P <.001). Overall, there were 22 (11%) adverse events, and 112 (57%) patients showed clinical improvement. When diltiazem was given outside of the existing protocol, the patients had higher rates of adverse events (18% versus eight percent; P = .033). Patients who received diltiazem in adherence with protocols were more likely to show clinical improvement (63% versus 46%; P = .031). Conclusion: This study suggests that prehospital diltiazem administration for AFIB with RVR is safe and effective when strict protocols are followed. Rodriguez A, Hunter CL, Premuroso C, Silvestri S, Stone A, Miller S, Zuver C, Papa L. Safety and efficacy of prehospital diltiazem for atrial fibrillation with rapid ventricular response. Prehosp Disaster Med. 2019;34(3):297–302.